TINJAUAN TENTANG PENGOLAHAN DAGING DI INSTALASI GIZI RUMAH SAKIT UMUM PUSAT DR. M. DJAMIL PADANG - Ernarita; Susgenti, Nelvi (Jurnal Pariwisata Bunda, 2023)
This research was motivated by the fact that some of the meat delivered by resellers did not fit into the good meat category, this was seen during processing, there was meat that had veins. Veined meat can affect the tenderness of the meat. The aim of this research is to increase insight, knowledge and experience regarding meat processing. The research method used is descriptive analysis. The data collection techniques used were observation, questionnaires and literature study. The results of this research show that meat processing is not in accordance with correct meat processing techniques, because there are still several problems such as meat not always being cut against the grain, and the correct temperature is not used during processing. Processing workers also do not thoroughly beat the meat before processing and do not marinate the meat to be processed.